Chlorophyll a, particulate organic carbon (POC), particulate organic nitrogen (PON), particulate organic phosphorous (POP) and Surfactants measurements from the central arctic ... - Robinson, Tiera-Brandy (PANGAEA, 2024)
As part of the MOCCHA 2018 campaign onboard I/B Oden, Sea surface microlayer (SML) and underlying water (ULW) samples were taken from an open lead system in the central arctic. Sampling occured during the autumn freeze-up from 18.08.18 - 08.09.18. Latitude ranged from 88.7644-89.5474 degrees and longitude ranged from 38.1087-45.7652 degrees as the ice pack moved over time, elevevation remained 0. Sea surface microlayer samples were collected using the glass plate technique (Harvey and Burzell, 1972, doi:10.4319/lo.1972.17.1.0156) via rotating glass disks equipped to a catamaran and underlying water samples were collected from 1 meter depth. Seven variables were sampled for; transparent exopolymer particles (TEP), coomassie stainable particles (CSP), surfactants, chlorophyll a, particulate organic carbon (POC), particulate organic nitrogen (PON) and particulate organic phosphorous (POP). Their concentrations are presented here in micrograms per litre. sea surface microlayer (SML) and undrlaying water (ULW) ...